Estimation of patient radiation dose from whole body 18F-FDG PET/CT examination in cancer imaging: a preliminary study - Mahmud, Mohd Hafizi; Nordin, Abdul Jalil; Ahmad Saad, Fathinul Fikri; Azman, Ahmad Zaid Fattah (IOP Publishing, 2014)
This study aims to estimate the radiation effective dose resulting from whole body fluorine-18 flourodeoxyglucose Positron Emission Tomography (18F-FDG PET) scanning as compared to conservative Computed Tomography (CT) techniques in evaluating oncology patients. We reviewed 19 oncology patients who underwent 18F-FDG PET/CT at our centre for cancer staging. Internal and external doses were estimated using radioactivity of injected FDG and volume CT Dose Index (CTDIvol), respectively with employment of the published and modified dose coefficients. The median differences of dose among the conservative CT and PET protocols were determined using Kruskal Wallis test with p < 0.05 considered as significant. The median (interquartile range, IQR) effective doses of non-contrasted CT, contrasted CT and PET scanning protocols were 7.50 (9.35) mSv, 9.76 (3.67) mSv and 6.30 (1.20) mSv, respectively, resulting in the total dose of 21.46 (8.58) mSv. Statistically significant difference was observed in the median effective dose between the three protocols (p < 0.01). The effective doses of whole body 18F-FDG PET technique may be effective the lowest amongst the conventional CT imaging techniques.